Characterisation of flare Soft X-ray distribution with solar magnetic activity. (May 2020) - Foldes, R; Berrilli, F
Abstract: We analyse the 0.1 — 0.8 nm solar soft X-ray flux catalogue from Geostationary Operational Environmental Satellites (GOES), managed by NASA/NOAA, between September 1978 and September 2017, in order to investigate the possible role of solar activity and solar cycle epoch on the distribution of soft X-ray peak fluxes. We concentrate our attention on the last three solar cycles because solar activity proxies seem to indicate a decrease in the magnetic activity of our star. We know that flare soft X-ray peak fluxes are characterised by a power-law distribution with an index α ≃ 2 that shows a minor dependence on solar cycle. More in detail, we study the dependence of the power-law parameters during each single solar cycle (cycles 21-24) and during different regimes of solar activity defined using three different proxies: i ) Sunspot Number (SSN), ii ) Mg II core-to-wing ratio (Mg II Index), and iii ) solar radio flux at 10.7 cm or 2800 MHz (F10.7). The power-law estimation analysis is performed in maximum likelihood estimation (MLE) fitting method with goodness-of-fit based on Kolmogorv- Smirnov test. Preliminary results indicate that the power-law index shows a slight decrease as solar activity decreases. This except for the F10.7 proxy. More in-depth statistical analysis is necessary to confirm our findings. A post-publication change was made to this article on 22 Jun 2020 to correct the webpage title to match the pdf.